Wellness, Fitness, Body Composition, Training and Performance Monitoring to Improve Athletes Life Quality - Oliveira, Rafael; Brito, João (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present reprint presents information to update the state of the art in professional and recreational, male and female athletes of different sports (e.g., soccer, speed skating, triathlon, strength training, and pole dancing). Moreover, it addresses some gaps in the literature, such as immunological and hormonal responses, body composition effects, and well-being/wellness. Notwithstanding, this reprint contributes information to improve load monitoring practices (of training and competition) and quality of life through direct or indirect research.